Motherhood and breastfeeding after brest carcinoma - Valent, Dragana (General Practice, 2024)
Introduction. Breast cancer is the most prevalent cancer in women. The most reliable method to diagnose breast cancer is through mammography, combined with ultrasonography or magnetic resonance imaging. The treatment plan may include surgery, radiation therapy, chemotherapy, hormone therapy, targeted therapy, or immunotherapy. Case report. The following is a case report of a 46-yearold woman who visited a physician in 2007 when she was planning her second pregnancy. She was 30 years old at the time. During a routine breast self-examination, she noticed a lump and was sent for an ultrasound examination where the tumor was confirmed. After diagnosis and preoperative preparation, she underwent breast-preserving surgery of the left breast, along with axilla dissection due to positive lymph nodes. Pathohistologic findings confirmed Carcinoma mixtus praecipue ductale G2 et partim mucinosum G2, while no metastatic changes were found in the axillary lymph nodes. The tumor’s hormonal status was estrogen 1, progesterone 1, and HER2 2. The patient received six rounds of FAC chemotherapy followed by 16 rounds of trastuzumab. After starting on tamoxifen and using it until December 2009, she had to undergo the removal of her right ovary due to the discovery of numerous cysts. Several cysts were also found on the left ovary. Five years after her breast cancer surgery, the patient became pregnant and gave birth to a baby girl. She breastfed her for ten months from the breast that was not operated on. Conclusion. Breast cancer is a serious illness that can greatly affect the reproductive health of young women. It is essential to take into account the patient’s desire to have children after treatment. Therefore, it is crucial to provide appropriate therapy and counseling.